Patients with chronic autoimmune thyroiditis are not at higher risk for developing clinically overt thyroid cancer: a 10-year follow-up study. Issue 3 (September 2020) - Rotondi, Mario; Groppelli, Gloria; Croce, Laura; Latrofa, Francesco; Ancona, Giuseppe; Coperchini, Francesca; Pasquali, Daniela; Cappelli, Carlo; Fugazza, Alessandro; Guazzoni, Valeria; Radetti, Giorgio; Chiovato, Luca
Abstract : Objective: : The association between chronic autoimmune thyroiditis (CAT) and differentiated thyroid cancer (DTC) remains controversial. The incidence of DTC increases when screening procedures are implemented, as typically occurs in CAT patients being routinely submitted to thyroid ultrasound (US). The aim of this study was to longitudinally evaluate the long-term development of DTC in patients with CAT. Design and methods: : A retrospective longitudinal cohort study was designed. For the study, 510 patients with chronic autoimmune thyroiditis (CAT) with a 10-year follow-up were enrolled. Patients were divided in two groups according to the presence (CAT+ NOD+; n = 115) or absence (CAT+ NOD−; n = 395) of co-existent nodules at diagnosis. The main outcome measures were appearance of new thyroid-nodules and development of DTC during follow-up. Results: : During a 10-year median follow-up period, new thyroid-nodules were detected in 34/115 (29.5%) patients in the CAT+ NOD+ group and in 41/395 (10.3%) in the CAT+ NOD− group ( P < 0.001). Logistic regression analysis showed that thyroid-volume at diagnosis and belonging to the CAT+ NOD+ group significantly predicted the appearance of a new thyroid nodule during follow-up, independently of baseline age and sex. Among the 75 patients experiencing the appearance of a new nodule, 27 (39%) met the criteria for fine-needle-aspiration-cytology (FNAC). A benign cytological diagnosis was rendered in all cases. Conclusions: : In our series of CAT patients, the appearance of new thyroid-nodules was frequent, but none of them were found to be malignant. The presence of CAT appears to be associated with a negligible risk of developing clinically overt DTC.